Brain and gastrointestinal cholecystokinin receptor family: structure and functional expression. - Wank, S A (1992)
Cholecystokinin was one of the first gastrointestinal peptides discovered in the mammalian brain. In the central nervous system there is evidence for CCKA and CCKB receptor subtypes. The CCKA receptors occur in a few localized areas of the central and peripheral nervous systems where they modulate feeding and dopamine-induced behavior. CCKB receptors occur throughout the central nervous system where they modulate anxiety, analgesia, arousal, and neuroleptic activity. We have recently purified and cloned a CCKA receptor cDNA from rat pancreas that allowed isolation of an identical cDNA from rat brain by using the polymerase chain reaction. Using low-stringency hybridization screening of cDNA libraries from rat brain and AR42-J cells, which possess large numbers of CCKB receptors, we identified previously unreported cDNAs, the sequence of which were identical in both tissues. The cDNA sequence encodes a 452-amino acid protein that is 48% identical to the CCKA receptor and contains seven transmembrane domains characteristics of guanine nucleotide-binding regulatory protein-coupled receptors. COS-7 cells transfected with this cDNA expressed binding sites for agonists and antagonists characteristic of a CCKB receptor subtype. We conclude that this cDNA isolated from rat brain and AR42-J cells is a receptor of the CCKB subtype and that the respective cDNAs for both CCKA and CCKB are identical in the brain and gastrointestinal system.